PENGARUH BIMBINGAN BELAJAR TERHADAP KECEMASAN SISWA DALAM MENGHADAPI UJIAN NASIONAL - Millatina, Amila (Universitas Sahid Surakarta, 2014)
Student anxiety in the face of National Examination is a fear of failure when the National Examinations can do well. The feeling can occur because of a lack of preparation optimal.Tujuan of this study was to investigate the influence of tutoring on student anxiety in the face of National Examination and to determine the level of anxiety of students in the face of the National Exam. The hypothesis is no influence of tutoring on student anxiety in the face of the National Exam.The subjects used in this study were male and female students MTsN Tinawas Nogosari Boyolali class IX. Grouping is done by screening participants. The experimental group 1 is a group of private tutoring, experimental group 2 is the regular tutoring group (group), while the control group is a group that does not follow the guidance of learning. Participants retrieval techniques using non-random sampling technique is purposive sampling techniques ie without giving an equal chance on the subject that are members of the population. Collecting data using the anxiety scale face the National Examination.Based on the analysis Anava KW between experimental groups 1, 2 experimental group and a control group of H = 12.817; p = 0.002 (p <0.01). This is also indicated by the average of the experimental group 1 amounted to 15.563, then the average of the experimental group 2 at 24.656 and 33.281 average for the control group. These results prove the existence of differences between the experimental groups 1, experiment 2, and the control group, which means that there are differences in the level of anxiety among students who take private tutoring classes, group classes, and that does not follow the guidance of learning.